Os experitempos das crianças, professoras e responsáveis: experiências em tempos de ensino remoto na pandemia da COVID-19 - Barros, Talita Vitória Santoro (Universidade Federal de São Carlos, 2022)
The year 2020 was marked by the untimely time of the SARS-Cov-2 virus pandemic. Dating back to Krónos time at the end of February, the virus arrived in Brazilian territory and manifested the political, economic and health imbalance that was already expected. The death toll was staggering and growing. Decrees, sanctions, ordinances were established to try to curb the movement of people and the high contagion of the coronavirus among the population. Social isolation - recommended by the World Health Organization (WHO) - was a restrictive measure adopted throughout the national scenario and for all ages. In view of this salute, all services and activities of a non-essential nature were temporarily closed, such as schools, churches, shopping, hotels, universities and some local businesses. Routines, plans, dreams and achievements were suspended to enter a kaíros time of the pandemic. With the closing of schools, the school reality of Brazilian children was adapted to the modality of remote teaching, as an exceptional strategy for the continuation of the school year. However, access and the opportunity to attend online education is dependent on resources, equipment and help from family members and/or guardians who can help children handle the tools and carry out activities. And this reality of transforming residence into the minimum conditions of a classroom is not available to millions of Brazilians (PNAD, 2018; IBGE, 2018, 2020). In this way, seeking to understand the experiences of children, teachers, family members and/or guardians who have experienced remote teaching in times of a pandemic, we carried out this research with a private school that presented the minimum and hypothetically ideal conditions for the offer of remote classes with a cutout established between the school years from the 1st to the 5th year of elementary school I. With cartographic inspirations and following the safety protocols due to the COVID-19 pandemic, our contact with the research subjects took place in a virtual way, with a directed questionnaire for teachers and another for family members and/or accountable about their experiences with remote teaching in times of a pandemic, and with online meetings with children through the Microsoft Teams platform. In all, we had the participation of nine (9) teachers, thirty-eight (38) family members and eighty-three (83) children. All the experiences that were written, shared or said, we describe them within a concept that we call experitempos (LEITE, 2013), as a junction of words between experience and time, since, we consider that the experiences of the COVID-19 pandemic are unique to this context. All experiments were presented and subjugated in themes emerged in theoretical and political reflections on childhood and children's rights in times of pandemic, such as issues related to child socialization, meeting children's needs, school education, and other lines that they crossed gender discussions, valuing teachers, relationship between school and family and others. The arguments were directed towards looking at and thinking about the child as a subject of law that needs to be present in the school's territory, and the school as an institution that must offer and contemplate all children's dimensions that were impassive to be assisted in remote teaching. Based on these experiences, we recognize the importance of discussing the experiences conceived during the COVID-19 pandemic – especially for children – in conjunction with educational policy proposals, so that government concerns do not overturn the school education of children in the schools.
The experiences of children, teachers and responsible: experiences in remote teaching times in the COVID-19 pandemic
Keywords: Experiência; Pandemia da COVID-19; Ensino Remoto; Educação de crianças; Experience; COVID-19 Pandemic; Remote Teaching; Education of children; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO